THE AUTHOR’S EXPLICIT PRESENCE IN A NARRATIVE TEXT: THE AUTHOR’S OPINION ABOUT THE CONTEMPORARY WORLD - O. S. Fedotova (Vestnik MGIMO-Universiteta)
The paper shows that the author of a narrative text might interrupt the course of fictional action to express his view of the situation. The diachronic analysis of English emotive prose proves that the author is always present in the text, be it the 19C, 20C, or the beginning of the 21C. One of the topics of the author’s dialogue with the reader may cover peculiarities of the contemporary world. The problems discussed are very much the same in different time periods. The analysis of English novels shows that authors usually give evaluation of the surrounding world which is far from ideal and which is full of difficulties, obstacles and disappointments. The difference lies in the forms of address of the author to the reader. In the novels of the end of the 18C and the beginning of the 19C the author usually acts as a personage who speaks directly to the reader. That’s why forms of direct address and personal pronouns mark this period. At the end of the 20C – at the beginning of the 21C the author’s comments are more laconic and are usually presented in the form of a maxim. Time shift is characteristic of all time periods discussed.